2018
DOI: 10.3390/nu10101457
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota’s Relationship with Liver Disease and Role in Hepatoprotection by Dietary Natural Products and Probiotics

Abstract: A variety of dietary natural products have shown hepatoprotective effects. Increasing evidence has also demonstrated that gut microorganisms play an important role in the hepatoprotection contributed by natural products. Gut dysbiosis could increase permeability of the gut barrier, resulting in translocated bacteria and leaked gut-derived products, which can reach the liver through the portal vein and might lead to increased oxidative stress and inflammation, thereby threatening liver health. Targeting gut mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 116 publications
(134 reference statements)
1
66
0
Order By: Relevance
“…In gut microbiota transplantation studies, germ-free C57BL/6J mice receiving intestinal bacteria from HFD-fed mice with high blood glucose were prone to develop liver steatosis and insulin resistance compared with counterparts that were transplanted with bacteria from healthy mice (Aron-Wisnewsky et al, 2013). Different degrees of liver pathology have also been linked with the different varieties of gut microbiota (Meng et al, 2018). Human studies have indicated that the abundance of Bacteroidetes in nonalcoholic fatty liver disease patients is much lower than that in simple steatosis and healthy groups (Fukui, 2015).…”
Section: The Causative Role Of Akkermansia Muciniphila In Liver Disormentioning
confidence: 99%
“…In gut microbiota transplantation studies, germ-free C57BL/6J mice receiving intestinal bacteria from HFD-fed mice with high blood glucose were prone to develop liver steatosis and insulin resistance compared with counterparts that were transplanted with bacteria from healthy mice (Aron-Wisnewsky et al, 2013). Different degrees of liver pathology have also been linked with the different varieties of gut microbiota (Meng et al, 2018). Human studies have indicated that the abundance of Bacteroidetes in nonalcoholic fatty liver disease patients is much lower than that in simple steatosis and healthy groups (Fukui, 2015).…”
Section: The Causative Role Of Akkermansia Muciniphila In Liver Disormentioning
confidence: 99%
“…Some probiotics contributes to increased antioxidants, exopolysaccharides, bioactive proteins, fermented lyases and enzymes activity in modulation of oxidative stress, protecting cells against induced damage by carcinogens and reactive oxygen species generated during body metabolism (Meng et al, 2018). Glutathione, glutathione reductase, s-transferases, glutathione peroxidases, super-peroxide dismutase and catalase are among beneficial probiotics antioxidant enzymes involved in the complex skin antiaging mechanism (Cinque et al, 2017).…”
Section: Probiotics Application In Cosmeticsmentioning
confidence: 99%
“…The GM is known to be correlated with human health (Hooper, Littman, & Macpherson, ; Meng, Li, Li, Gan, & Li, ). In the present study, an interesting feature of the GM in the nomads in northern Xinjiang was that the Firmicutes to Bacteroidetes (F/B) ratio was extremely high, up to 5.2.…”
Section: Discussionmentioning
confidence: 99%